Need Analysis for Developing ELT Material for Early Childhood Education at UIN Alauddin Makassar - Lestari, Erfyanti Ayu; Said, Abdul Muis (English Language Teaching for EFL Learners Journal, 2024)
This research investigated the need of English that is Learning Needs and Linguistik Needs for Early Childhood Education Department at UIN AlauddinMakassar. This study involved 42 respondents which consists of 38 students, 1 lecturer, and 3 graduates Early Childhood Education Department at UIN AlauddinMakassar. In collecting the data, questionnaire and interview were employed by the researcher. The collection of the data was done by distributing the questionnaires to the participants to identify the students‟ needs in Early Childhood Education Department and interview guideline to find additional data. The findings indicated that the students' ability levels of all components of English (reading, writing, speaking, listening, grammar and vocabulary) are at the 'adequate' level. The order of students' preferences related to the English component is; Speaking and Vocabulary, which gained 3.35 of average score. level of other components of English, such as; Listening only reached 3.23 of average score, reading (3.22), writing and grammar (3.20). Meanwhile, the difficulties experienced by students while learning English were Inadequate knowledge of grammar (3.21). In addition, the most preferred learning style by students is film and video (3.24) and the most popular learning preference is speaking with a score of (3.20). This study also provides goals and objectives as a reference in designing and developing appropriate English language materials for Early Childhood Education.The goals that had been formulated are (1) to help students communicate effectively in English by developing students‟ English components and (2) to equip students to have a good basicfoundation in English which enables them to communicate everyday situations and topics. Besides, the formulated objectives are students able to use English components practically through topics related to the department with various learning preferences and styles.Objectives of this research;(1) This students are able to discuss,practice,andgive example about teaching reading for children using related vocabulary correctly.(2) The students are able to comprehend intermediate level reading materials related to children learning a foreign language and actively discuss it to their peers.(3) The students are able to practice teaching English with media using story book communicatively in small group.(4) The students are able to classify and explain about learning tools for early agr learners and conclude the topic in spoken and written English.(5) The students are able to understand and discuss clearly the way of teaching listening for children and give reason of how important to administer education.(6) The students are able to give clear presentation related to teaching English with media songs and practice with their listening.(7) The studentsare able to practice teaching English with media film cartoon in role play.(8) The students are able to participate actively in discussion related to the most appropriate English for early age lessons plans and give proper reason to their point of view.(9) The students are able to understand clear children development and characteristics and discuss their preferences towards the topic.